Posterior Rotational and Translational Stability in Acromioclavicular Ligament Complex Reconstruction: A Comparative Biomechanical Analysis in Cadaveric Specimens. Issue 10 (August 2020) - Morikawa, Daichi; Huleatt, Joel B.; Muench, Lukas N.; Kia, Cameron; Berthold, Daniel P.; Cote, Mark P.; Obopilwe, Elifho; Kelolli, Denis; Scheiderer, Bastian; Mazzocca, Augustus D.
Background: Persistent posterior instability of the acromioclavicular (AC) joint is a reported complication after isolated coracoclavicular (CC) reconstruction. Thus, multiple techniques have been proposed attempting to restore biomechanics of the AC ligament complex (ACLC). Purpose/Hypothesis: The purpose was to evaluate the posterior translational and rotational stability of an ACLC reconstruction with a dermal allograft (ACLC patch) as compared with 3 suture brace constructs. It was hypothesized that the ACLC patch would better restore AC joint posterior stability. Study Design: Controlled laboratory study. Methods: A total of 28 cadaveric shoulders (mean ± SD age, 57.6 ± 8.3 years) were randomly assigned to 1 of 4 surgical techniques: ACLC patch, oblique brace, anterior brace, and x-frame brace. The force and torque to achieve 10 mm of posterior translation and 20° of posterior rotation of the AC joint were recorded in the following conditions: intact, transected ACLC, ACLC patch/brace repair, ACLC patch/brace repair with dissected CC ligaments, and ACLC patch/brace repair with CC ligament repair. Results: For posterior translation, transection of the ACLC reduced resistance to 16.7% of the native. With the native CC ligaments intact, the ACLC patch (59.1%), oblique brace (54.1%), and anterior brace (60.7%) provided significantly greater stability than the x-frame brace (33.2%; P < .001, P = .008, P < .001, respectively). ACLC patch, oblique brace, and anterior brace continued to have significantly higher posterior translational resistance than the x-frame (35.1%; P < .001, P = .003, P < .001) after transection and subsequent CC ligament repair. For posterior rotation, transection of the ACLC decreased the resistance to 5.4% of the intact state. With the CC ligaments intact, the ACLC patch (77.1%) better restored posterior rotational stability than the oblique (35.3%), anterior (48.5%), and x-frame (23.0%) brace repairs ( P < .001, P = .002, P < .001). CC ligament transection and subsequent repair demonstrated the ACLC patch (41.0%) to have improved stability when compared with the oblique (16.0%), anterior (14.0%), and x-frame (12.7%) repairs ( P = .006, P = .003, P = .002). Conclusion: ACLC reconstruction with a dermal allograft better restored native posterior rotational stability than other brace constructs, with translational stability similar to the oblique and anterior brace technique at the time of surgery. Clinical Relevance: Horizontal stability of the AC joint is primarily controlled by the ACLC. Inability to restore AC joint biomechanics can result in persistent posterior instability and lead to functional impairment.